Ambiente térmico y bienestar de los cerdos en el período de descanso previo al sacrificio - Centurión, R. A.O.; Caldara, F. R.; Moi, M.; Almeida Paz, I. C.L. [UNESP]; Garcia, R. G.; Nääs, I. A.; Alves, M. C.F.; Zeviani, W. M.; Seno, L. O. (My University, 2014)
The research aimed to evaluate the relationship between the thermal environment of the rest pens in a pig slaughterhouse and the surface temperature (ST) of the animals as well as the effect of intermittent water spraying on thermal comfort. There were two visits to slaughter industrial being in each selected three pens of rest, one for control treatment (no spray throughout the period) and two for the treatment of intermittent spraying water (30 minutes intervals with constant spray followed by 30 minutes then turned off). Assessments began at the time of discharging animals in which are taken the thermographic images from lots using an infrared thermographic camera. After housing in the pens, were registered the thermographic images and the respiratory frequency (RF) every five minutes for four hours. Were evaluated the temperature, relative humidity and temperature-humidity index (THI). Considering the values of THI was observed that the animals remained in a condition of comfort only at the time of his arrival at the slaughterhouse. The ST and RF of the animals kept in the pens without sprinkler system (control) showed a linear increase in function of time of day, with increasing temperature. The treatment with intermittent sprinkling of water was observed oscillatory behavior of the ST and RF, however it was always lower than the control treatment, even in times when the water sprinklers were turned off. The time required of spray to reduction and stabilization of the ST of the animals was limited to the combination of temperature and relative humidity, being estimated at 25 minutes at times of higher THI. The maximum environmental temperature during evaluation was 28.4 °C.
Thermal environment and welfare of pigs in the resting period before slaughter
Keywords: Infrared thermography; Spraying; Thermal comfort